Relative Impact of the U.S. Energy Market Sentiments on Stocks and ESG Index Returns: Evidence from GCC Countries - Verma, Rahul; Mohnot, Rajesh (International Journal of Energy Economics and Policy, 2023)
In this study, we provide empirical evidence on the relative impact of energy market sentiments on the stock and ESG index returns in the U.S. and Gulf Cooperation Council (GCC) economies. Specifically, we study movements in four distinct categories of energy sentiments (natural gas, crude oil, RBOB gasoline, and heating oil) displayed by professional investors and investigate their relative impact on ESG investments and stock returns in the U.S. and GCC economies. We employ the recently developed automatic time series forecasting methodology Autometrics to examine the postulated relationships. The results of the regression models suggest that there is a significant negative impact of stock sentiments and a positive impact of energy sentiments on the S&P 500 returns. However, in the case of the U.S. energy companies’ returns, there are significantly higher effects of only energy market sentiments (mainly crude oil and RBOB gasoline). In the case of the GCC stock markets, there are significant positive impacts of crude oil sentiments and the S&P 500 of varying degrees of strength. The most significant impact of crude oil sentiments is observed in UAE and Saudi Arabia and is almost of the same magnitude as those on the U.S. energy companies’ returns. These results are consistent with arguments provided in behavioral finance studies that investors prefer bigger profits over social returns during bullishness and step back from social investing when better investment opportunities are available. Also, ESG investing may be preferred during bearishness by utilitarian investors to generate abnormal returns during such lean periods.